Cover Studies (okładkoznawstwo) — Old Issue, New Research Conception - Łubocki, Jakub Maciej (Zagadnienia Rodzajów Literackich / The Problems of Literary Genres, 2020)
The article explores the term ‘cover’ which is redefined and contraposed with the term ‘bookbinding’ against the background of various research perspectives. Research on the protective elements of documents is divided between bookbinding studies, binding studies (bibliopegy) and cover studies. The conception of the consolidation of research conducted on the covers of various types of documents within cover studies (okladkoznawstwo) is discussed. The history of this field of study, the basic frameworks and the terms which assist the development of this field, as well as postulations for the future and goals to be achieved are also presented.